Reação de genótipos de triticale ao Soil borne wheat mosaic virus (SBWMV) - Toledo, Karina Grando (2010)
The wheat mosaic caused by the Soil borne wheat mosaic virus (SBWMV) is vectored by the plasmodiophoromycete Polymyxa graminis Led., which survives in soil as resting spores and infects plant roots by means of zoospores released under favorable ambient conditions. Wheat mosaic occurs worldwide as a limiting factor to winter cereals, including triticale. The disease damage results from either single or mixed virus infections. It s control is usually restricted to resistant cultivars and to scheduling of the sowing date. The virus identification is usually performed by serological tests, although some cases may require more sensitive techniques such as RT-PCR. In 2008, there was a significant increase of wheat mosaic incidence in the Planalto Médio of Rio Grande do Sul state, in southern Brazil. Therefore, some studies were carried out at the Embrapa Trigo experimental field, in Passo Fundo county, to evaluate the effect of SBWMV on triticale genotypes, including assessments of total soluble protein, total soluble sugar, chlorophyll content, peroxidase activity, incidence and disease index, as well as plant agronomic traits. Data were subjected analysis of variance and comparison of means by Tukey test at 5% significance. All assessed 4 variables performed different in SBWMV infected plants. For instance, the peroxidase activity was higher, which shows the disease causes high level of stress. The disease increased gradually and it was more severe in genotypes whose symptoms appeared in early plant growth stages